Postchemotherapy changes in testicular germ cell tumours: biology and morphology. Issue 1 (January 2017) - Berney, Daniel M; Lu, Yong‐Jie; Shamash, Jonathan; Idrees, Muhammad
Abstract : Advances in modern chemotherapy and targeted treatments have resulted in lengthened survival in a variety of tumour types in the last decade. Increasingly in the 21st century, postchemotherapy resections are considered as a possible mode of treatment. Due to their exquisite chemosensitivity, resection of postchemotherapy masses has long been part of the armamentarium of treatment in testicular germ cell neoplasia, which has resulted in a variety of new morphological variants being described after treatment. Here we discuss the possible reasons for germ cell tumour chemosensitivity and hypotheses on the biological pathways leading to resistance to treatment, as well as an outline of the diverse morphology of those tumours which prove recalcitrant to standard treatment methods. The large range of morphologies and their diagnostic challenges may throw light upon the future problems to be encountered in non‐germ cell solid tumour pathology, as the resection of postchemotherapy masses becomes increasingly important in patient management.